An econometrical estimation of the demand for money in South Africa : the long-run function during the period 1918-60 - Maxwell, Thomas (Rhodes University, Faculty of Commerce, Department of Economics, 2026)
Introduction: In recent years there has been a marked upsurge in the output of literature dealing with the demand for money, but with the exception of the North American Continent, empirical research has lagged distressingly far behind the voluminous output of theory. This dearth of empirical results has had a restrictive influence. Since any of the controversial points which are being disputed by theoreticians can only be resolved by recourse to empirical methods. The restriction of empirical research to the North American Continent has further meant that the various points under dispute have had only a limited qualification and consequently monetary theorists have had no indication as to the universalizability of their conclusions. There is thus a great need for empirical studies in other countries so that the validity of the rival theories can be tested under different conditions. It was with these thoughts in mind that the present study was undertaken. Its objectives are strictly national and no pretense of strict international comparability is made. Further, great care has been taken to avoid the pitfall so beloved of econometricians, the fallacy of reduction wherein strictly limited results are uncritically universalized. Thus no attempt has been made to draw conclusions which will have universal validity. The theoretically vital points which are going to be examined in the light of South African experience are: 1. The feasibility of distinguishing idle from active balances, and if this proves possible, the determination of the wealth and interest elasticities of these balances
Keywords: Econometrics; Keynesian economics; Demand for money -- South Africa